The Practice of Using Inheritance Assets for Death Feast Expenses from the Perspective of Islamic Law and the Aceh Customary Council (Majelis Adat Aceh) - Lembong, Suarto; Tanjung, Dhiauddin; Siregar, Ramadhan Syahmedi (International Journal of Science and Society, 2024)
This study aims to determine the practice of using pre-divided inheritance as funeral expenses in Aceh Singkil Regency from the perspective of Islamic Law and the Aceh Customary Council (Majelis Adat Aceh). This study uses a qualitative method with data collection techniques in the form of observation, interviews, and documentation studies. The results of the study found that funeral expenses in Aceh Singkil Regency are often carried out using undistributed inheritance, even though this is contrary to Islamic law. Islamic law prohibits the use of inheritance for funerals except under certain conditions with strict requirements, but the practice in Aceh Singkil shows that many of these requirements are not met. In addition, the view of the Aceh Singkil Regency Customary Council emphasizes that the use of undistributed inheritance for funerals is contrary to sharia and is very relevant. Therefore, the implementation of this prohibition is very important to prevent violations of Islamic Law.